Pengaruh Pemberian POC Buah Maja dan Pupuk Kotoran Kambing terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) pada Sistem Polybag - Rohmad Purwanto; Pramono Hadi; Libria Widiastuti (MAN 4 Kota Pekanbaru, 2026)
Pakcoy (Brassica rapa L.) is an economically important leafy vegetable that has potential for organic production. The application of liquid organic fertilizer (POC) from maja fruit with goat manure will have positive impact on plant growth, yield and soil fertility improvement. This research was conducted to analyze the inﬂuences of POC from maja fruit concentration, goat manure dose, and its interaction on the growth and yield of pakcoy. The research was conducted at the village of Ngadirejo, District of Kartasura, Regency of Sukoharjo in the hamlet of Klinggen from December 2025 to January 2026. A 2-factor, 3-replication factorial CRD was used for this study. The 1st factor was the concentration of POC from maja fruit, ie (M1; 10, M2; 20, and M3; 30) ml/L, and the 2nd factor was goat manure rate ie (K1; 500, K2; 750, and K3; 1000) g/polybag) as followed by 250g of goat manure into each concentration. Plant height, leaf width, fresh weight, and root volume were observed. Data were subjected to analysis of variance (ANOVA) and further subjected to DMRT at 5% level of significance whenever significant F values obtained. The K factor had a significant effect on leaf width, while other parameters were not significantly different.